Enxofre foliar em V4, V8 e V12 no milho safrinha e inoculação da soja em função do tipo do produto e forma de aplicação - Veiga, Bruno Conceição de (2021)
One of the factors that influence crop productivity is the deficiency of some essential nutrients. Sulfur is the fourth main element demanded by the culture, with recognized importance in mineral nutrition, mainly due to its participation in enzymes and proteins. Sulfur is demanded by agricultural crops with grain yield in quantities similar to phosphorus, ie, 10 to 30 kg ha-1 , but it does not receive the same attention in annual fertilization. In light of the above, the objective of this study was to evaluate, under field conditions, the agronomic performance of off-season corn submitted to sulfur application via the leaf, combining different doses and phenological stages. Nitrogen (N), a macronutrient for plants, has a structural function in most living organisms, consisting basically of amino acids, proteins, nucleic acids and a chlorophyll molecule, when it comes to plants. This is found in the atmosphere in large quantities, but in a non-soluble form for plants, and in the soil the supply can occur through organic matter, being a problem in Brazil, which presents soils with low levels of organic matter. The supply of N2 (atmospheric) can be provided through the biological fixation process, promoted by bacteria of the genus Bradyrhizobium when inoculated in seeds. Therefore, the objective was to evaluate the agronomic performance of soybean inoculated with the genus Bradyrhizobium as a function of the sowing furrow application form and traditional inoculation application via seed, using two product sources, liquid and peat under different doses.